Knowledge transfer from international joint ventures to local suppliers in a developing economy - Khan, Zaheer; Shenkar, Oded; Lew, Yong Kyu (Journal of International Business Studies, 2015)
Using in-depth data from 155 Pakistani auto components suppliers, we study the role of socialization in knowledge transfer from international joint venture assemblers. We find that whereas formal socialization mechanisms enhance the comprehension and speed of knowledge transfer to local suppliers, informal socialization mechanisms enhance comprehension but not speed. Building on structural contingency theory, we find that having a mechanistic organizational structure among knowledge recipients is an antecedent to formal socialization, leading to improved knowledge transfer.